Neutrophil extracellular traps, disease severity, and antibiotic response in bronchiectasis: an international, observational, multicohort study. Issue 8 (August 2021) - Keir, Holly R; Shoemark, Amelia; Dicker, Alison J; Perea, Lidia; Pollock, Jennifer; Giam, Yan Hui; Suarez-Cuartin, Guillermo; Crichton, Megan L; Lonergan, Mike; Oriano, Martina; Cant, Erin; Einarsson, Gisli G; et al.
Summary: Background: Bronchiectasis is predominantly a neutrophilic inflammatory disease. There are no established therapies that directly target neutrophilic inflammation because little is understood of the underlying mechanisms leading to severe disease. Neutrophil extracellular trap (NET) formation is a method of host defence that has been implicated in multiple inflammatory diseases. We aimed to investigate the role of NETs in disease severity and treatment response in bronchiectasis. Methods: In this observational study, we did a series of UK and international studies to investigate the role of NETs in disease severity and treatment response in bronchiectasis. First, we used liquid chromatography-tandem mass spectrometry to identify proteomic biomarkers associated with disease severity, defined using the bronchiectasis severity index, in patients with bronchiectasis (n=40) in Dundee, UK. Second, we validated these biomarkers in two cohorts of patients with bronchiectasis, the first comprising 175 patients from the TAYBRIDGE study in the UK and the second comprising 275 patients from the BRIDGE cohort study from centres in Italy, Spain, and UK, using an immunoassay to measure NETs. Third, we investigated whether pathogenic bacteria had a role in NET concentrations in patients with severe bronchiectasis. In a separate study, we enrolled patients with acute exacerbations of bronchiectasis (n=20) in Dundee, treated with intravenous antibiotics for 14 days and proteomics were used to identify proteins associated with treatment response. Findings from this cohort were validated in an independent cohort of patients who were admitted to the same hospital (n=20). Fourth, to assess the potential use of macrolides to reduce NETs in patients with bronchiectasis, we examined two studies of long-term macrolide treatment, one in patients with bronchiectasis (n=52 from the UK) in which patients were given 250 mg of azithromycin three times a week for a year, and a post-hoc analysis of the Australian AMAZES trial in patients with asthma (n=47) who were given 500 mg of azithromycin 3 times per week for a year. Findings: Sputum proteomics identified that NET-associated proteins were the most abundant and were the proteins most strongly associated with disease severity. This finding was validated in two observational cohorts, in which sputum NETs were associated with bronchiectasis severity index, quality of life, future risk of hospital admission, and mortality. In a subgroup of 20 patients with acute exacerbations, clinical response to intravenous antibiotic treatment was associated with successfully reducing NETs in sputum. Patients with Pseudomonas aeruginosa infection had a lessened proteomic and clinical response to intravenous antibiotic treatment compared with those without Pseudomonas infections, but responded to macrolide therapy. Treatment with low dose azithromycin was associated with a significant reduction in NETs in sputum over 12 months in both bronchiectasis and asthma. Interpretation: We identified NETs as a key marker of disease severity and treatment response in bronchiectasis. These data support the concept of targeting neutrophilic inflammation with existing and novel therapies. Funding: Scottish Government, British Lung Foundation, and European Multicentre Bronchiectasis Audit and Research Collaboration (EMBARC).